2020
DOI: 10.1002/hed.26468
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic factors in patients with advanced head and neck cancer treated with radiation therapy

Abstract: Background: Approximately 50% of patients with head and neck cancer (HNC) initially were seen with advanced disease. We aimed to evaluate the association of epidemiologic factors with advanced HNC at diagnosis. Methods: The OraRad multicenter prospective cohort study enrolled HNC patients receiving curative-intent radiation therapy. Factors assessed for association with advanced HNC presentation at diagnosis included demographics, social and medical history, cancer characteristics, human papilloma virus (HPV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Regarding periodontal disease and dental caries status, our sub-cohort is similar to that of the larger OraRad cohort ( Table 1 and Brennan et al, 2021 ). A study identified by LitSuggest, reviewing findings pertaining to oral HPV infection in relation to periodontitis, suggests periodontal pockets may act as a reservoir for HPV and that oral HPV prevalence may be associated with periodontitis ( Shigeishi et al, 2021a ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Regarding periodontal disease and dental caries status, our sub-cohort is similar to that of the larger OraRad cohort ( Table 1 and Brennan et al, 2021 ). A study identified by LitSuggest, reviewing findings pertaining to oral HPV infection in relation to periodontitis, suggests periodontal pockets may act as a reservoir for HPV and that oral HPV prevalence may be associated with periodontitis ( Shigeishi et al, 2021a ).…”
Section: Discussionsupporting
confidence: 58%
“…Demographics and clinical information of our HNC patient cohort ( N = 30 patients, sub-cohort of OraRad study) are presented in Table 1 . Clinical information, including caries and periodontal disease status for OraRad HNC patient cohort, associated with HPV status ( N = 559 of 572 total patients) has been published elsewhere ( Brennan et al, 2021 ). While no significant differences were noted in age and ethnicity, the male population was over-represented in the HNC patient set in OraRad and this study, as anticipated for oral SCC in general and for HPV-associated oropharyngeal cancers ( Fakhry et al, 2018 ; Mahal et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies describe the epidemiological profile of head and neck cancer (HNC) patients in different parts of the world. Age, sex, race, socioeconomic status, marital status, and primary tumor location are factors commonly reported (Lebo et al,2019;Brennan et al,2021). The present study identified the following data: sex, age, occupation, alcohol and tobacco use, tumor location, treatment type, and possible adverse effects of oral cavity treatments, allowing the comparison of findings from two regions of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Primary RT sites of larynx/ hypopharynx or oral cavity were associated with worsening DMFS over time compared to both the oropharynx and salivary glands. OraRad patients with human papillomavirus (HPV)positive oropharyngeal cancers (47% of the current cohort) differed in many ways from those with all other HNCs (Brennan et al 2021). Patients with HPV-positive oropharyngeal cancer had higher socioeconomic status (more education, increased likelihood of private medical and dental insurance, decreased likelihood of Medicaid, or receipt of public assistance), were more likely to be white and married, used tobacco less but used alcohol more frequently, and had less dental disease burden with more teeth at baseline and less periodontal disease.…”
Section: Discussionmentioning
confidence: 99%